2015
DOI: 10.1007/s13277-015-3688-4
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation of the cysteine protease RECK may cause metastasis of osteosarcoma

Abstract: The present study examined the role of reversion-inducing cysteine-rich protein with Kazal motifs (RECK) promoter hypermethylation as a causative factor in metastasis of osteosarcoma. Using human pathological samples, it is demonstrated that RECK, a cysteine protease that reversibly regulates expression of matrix metalloproteases like matrix metallopeptidase 9 (MMP9), is transcriptionally inhibited in osteosarcoma, especially metastatic variants. This result comes from its promoter hypermethylation, as evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…RECK is usually reported as a tumor suppressor, particularly an inhibitor of metastasis, in many types of cancer. 14 , 15 , 27 In this study, the suppressive effect of RECK on GC cells was confirmed, and RECK was inhibited by miR-590-5p. Additionally, other miRNAs, including miR-221, miR-222, miR-374-5p, and miR-25, also regulated RECK by binding to its 3′-UTR and contributing to the growth and invasion of GC.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…RECK is usually reported as a tumor suppressor, particularly an inhibitor of metastasis, in many types of cancer. 14 , 15 , 27 In this study, the suppressive effect of RECK on GC cells was confirmed, and RECK was inhibited by miR-590-5p. Additionally, other miRNAs, including miR-221, miR-222, miR-374-5p, and miR-25, also regulated RECK by binding to its 3′-UTR and contributing to the growth and invasion of GC.…”
Section: Discussionsupporting
confidence: 65%
“… 12 Loss of RECK is correlated with metastasis in lung cancer, hepatoblastoma, and osteosarcoma. 13 15 RECK inhibited tumorigenicity of GC by suppressing NOTCH1 signaling. 16 Hypoxia- and RAS-signaling cooperatively downregulated the expression of RECK, thereby promoting malignant cell behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These genes were hypermethylated in various types of tumors and were involved in tumor-associated biological processes. For example, promoter methylation of RECK contributes to metastasis of osteosarcoma (9). BRCA1 negatively mediates cell proliferation, and its mRNA levels were downregulated by methylation (10).…”
Section: Introductionmentioning
confidence: 99%
“…DNA hypermethylation in promoter is a key characteristic in cancer and it was considered to be able to silence the tumor suppressor genes to induce the development of cancer (14)(15)(16). Some DNA methylation was also observed in OS and found to be associated with its progression, the methylation level of RECK was gradually increased with the development of OS, while the opposite trend of its expres-sion profile was observed (17). In the study of Sonaglio et al, the differential ESR1 and p14ARF gene methylation profiles were also identified as prognostic indicators in OS (18).…”
Section: Introductionmentioning
confidence: 99%